Pengaruh Inovasi dan Harga terhadap Keputusan Pembelian pada Pengguna Tokopedia di Kota Bandung (Studi Kasus pada Produk Berlabel Dilayani Tokopedia) - Solihin, Ismail; Sadeli, Revael Ardy (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research test aims to see the influence of product and price innovation on the purchasing decisions of Tokopedia users in the city of Bandung. The thorough test used data collected from questionnaires using purposive sampling technique, the number of respondents was 100 people. This thorough test uses validity and reliability test instruments. The hypothesis in this study uses multiple linear regression, coefficient of determination, partial and simultaneous. The results obtained from this thorough test are that partially, Product Innovation and Price have a significant influence on Purchasing Decisions. The F test results show that the calculated f result is 61,338, which is more than the f table of 3.09. From this it can be said that Innovation and Price have a significant influence on Purchasing Decisions.